Hepatopulmonary Shunt Ratio Verification Model for Transarterial Radioembolization - Yeyin, Nami; Kesmezacar, Fahrettin Fatih; Tuncman, Duygu; Demir, Ozge; Uslu-Besli, Lebriz; Gunay, Osman; Demir, Mustafa (BENTHAM SCIENCE PUBL LTD, 2024)
Introduction: The most important toxicity of transarterial radioembolization therapy applied in liver malignancies is radiation pneumonitis and fibrosis due to hepatopulmonary shunt of Yttrium-90 (Y-90) microspheres. Currently, Technetium-99m macroaggregated albumin (Tc-99m-MAA) scintigraphic images are used to estimate lung shunt fraction (LSF) before treatment. The aim of this study was to create a phantom to calculate exact LFS rates according to Tc-99m activities in the phantom and to compare these rates with LSF values calculated from scintigraphic images. Materials and Methods: A 3D-printed lung and liver phantom containing two liver tumors was developed from Polylactic Acid (PLA) material, which is similar to the normal-sized human body in terms of texture and density. Actual %LSFs were calculated by filling phantoms and tumors with Tc-99m radionuclide. After the phantoms were placed in the water tank made of plexiglass material, planar, SPECT, and SPECT/CT images were obtained. The actual LSF ratio calculated from the activity amounts filled into the phantom was used for the verification of the quantification of scintigraphic images and the results obtained by the Simplicity(90)Y (TM) method. Results: In our experimental model, LSFs calculated from( 99m)Tc activities filled into the lungs, normal liver, small tumor, and large tumor were found to be 0%, 6.2%, 10.8%, and 16.9%. According to these actual LSF values, LSF values were calculated from planar, SPECT/CT (without attenuation correction), and SPECT/CT (with both attenuation and scatter correction) scintigraphic images of the phantom. In each scintigraphy, doses were calculated for lung, small tumor, large tumor, normal liver, and Simplicity(90)Y (TM). The doses calculated from planar and SPECT/CT (NoAC+NoSC) images were found to be higher than the actual doses. The doses calculated from SPECT/CT (with AC+with SC) images and Simplicity(90)Y (TM) were found to be closer to the real dose values. Conclusion: LSF is critical in dosimetry calculations of Y-90 microsphere therapy. The newly introduced hepatopulmonary shunt phantom in this study is suitable for LSF verification for all models/brands of SPECT and SPECT/CT devices.
Keywords: Lung shunt fraction; radionuclide dosimetry; hepatopulmonary phantom; Y-90 microsphere therapy; transarterial radioembolization; liver tumors; TC-99M MACROAGGREGATED ALBUMIN; Y-90 RADIOEMBOLIZATION; SPECT/CT; DOSIMETRY; Pharmacology & Pharmacy; Radiology, Nuclear Medicine & Medical Imaging